FAKTOR RISIKO LINGKUNGAN TERHADAP KEJADIAN STUNTING PADA ANAK - Akmal Akmal; Bakhrani A. Rauf; Andi Asmawati Azis; Rahmawati Azis (UNM Environmental Journals, 2022)
One of the problems faced by children under the age of 5 years is stunting. The adverse impact of the condition is that it can be damaged or difficult to achieve optimal physical and cognitive development. Stunting is not only caused by a lack of nutritional intake but can be caused by various factors including environmental factors. Risk factors for the living environment and parental behavior are one of the factors that greatly determine the occurrence of stunting in children. The purpose of the study is to describe environmental risk factors related to stunting events in children under five and create strategies that can be used to deal with these problems. This research uses a qualitative descriptive method with a case study approach carried out in Sudiang Raya Village, Biring Kanaya District, Makassar City. Data collection is carried out by means of observation, in-depth interviews, and document tracking. Qualitative data analysis uses content analysis to discuss in depth the data and information collected. The results showed that low environmental health knowledge, attitudes and behaviors, poor water source conditions and environmental sanitation, and low levels of welfare are factors that trigger the onset of stunting in children.